Alcalá de Henares in the European travel tales of 16th century: The perception of a Spanish city in the beginning of Early modern period - Gijón Jiménez, Verónica (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Alcala de Henares was already an important town when Francisco Jiménez de Cisneros chose it in order to found his new University. Since the creation of this institution in 1449 Cisneros supported a series of urban remodelling that transformed the town in one of the most prominent urban nuclei of the Peninsula. The good reputation of the University and the site of the town, close to an important communication route favoured that many foreign travellers visited it during 16th century. In this article I will study the image of the city through European travel literature of this century.